Survey of resistance to chloroquine by Plasmodium vivax in Indonesia. - Baird, J; Sustriayu Nalim, M; Basri, H; Masbar, S; Leksana, B; Tjitra, E; Dewi, R; Khairani, M; Wignall, F (1996)
In February 1995 we surveyed to chloroquine among patients with Plasmodium vivax malaria at Nias Island, in the Indian Ocean near north-western Sumatra, Indonesa. The subjects, 21 indigenous males and females (6-50 years old) infected with > 40 asexual blood stage parasites of P. vivax per microliter of blood, had mild symptoms or none at all. Seven of these patients had > 100 ng/mL whole blood chloroquine levels before the first supervised dose of chloroquine (3 doses of 10 mg/kg, 10 mg/kg, 5 mg/kg of base given at 24 h intervals). Whole blood chloroquine levels on the last day of dosing confirmed normal absorption (range 413-3248, mean 1141, SD 616 ng/mL). Blood films were examined on days 0, 2, 4, 7, 11, 14, 18, 21 and 28 after initiating therapy. Three patients had recurrent asexual P. vivax parasitaemias between days 14 and 18, despite effective levels of chloroquine in whole blood (> or = 100 ng/mL) at the time of recurrence. Resistance to standard chloroquine therapy by P. vivax appeared in 14% of infections among residents of Nias.